Lessons of Productive Learning in Hungary - Bárdossy, Ildikó; Dezső, Renáta Anna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Productive learning is a form of social learning based on an American modell (City as School, New York, 1972), which became widespread in Europe during Transition years (1989-90). Its implications in Hungary had that of a pioneer nature in the region. The specifi cs of this pattern in Pecs and its surroundings is that the attitudes of it have become present not only in some venues of public education but in various platforms of teacher education as well – suggesting the idea of inclusive schooling. Bardossy founded her relevant work in 1990 and she has been followed by her once student, now colleague, Dezso since 2010. The present study illustrates their work devoted to productive learning.